Pengaruh Faktor-Faktor Individual Dan Budaya Etis Organisasi Terhadap Perilaku Etis Mahasiswa Akuntansi (Studi Empiris Pada Mahasiswa Akuntansi di Perguruan Tinggi Kota Padang) - Fivi wulandari (Universitas Negeri Padang, 2015)
This study aims to obtain empirical evidence about the extent of the influence individual factors (emotional intelligence, spiritual intelligence, locus of control (LoC), equity sensitivity) and organizational ethical culture to the ethical attitude of accounting students in Padang city. This research study classified the causative. Population of this research are accounting students in Padang city Samples are selectedbased on purposive sampling method. There are 287 accounting students from 4 colleges in Padang city participated in this research. Methods ofdata collectionused questionnaire. Statistical analysis used multiple regression. The result of this study indicate (1)emotional intelligence has positive and significant on the ethical attitude of accounting students (2) spiritual intelligence has positive and significant on the ethical attitude of accounting students (3) locus of control has positive and significant on the ethical attitude of accounting students (4) equity sensitivity has positive and significant on the ethical attitude of accounting students (5) organizational ethical culture has positive and significant on the ethical attitude of accounting students. Keywords: Emotional Intelligence, Spiritual Intelligence, Locus of control, Equity Sensitivity, Organizational ethical culture, ethics.